Ocorrência de mastite clínica e subclínica causada por Trichosporon beigelii em um rebanho leiteiro - Victoria, Cassiano [UNESP]; Langoni, Hélio [UNESP] (My University, 2006)
Trichosporon beigelii was isolated from four and three Holstein heifers with clinical and subclinical mastitis respectively, during the extension activities of Nucleus of Mastitis Research - NUPEMAS - FMVZ - UNESP - BOTUCATU - BRAZIL. This fungus is considered extremely important because it is responsible for superficial skin infections, known as white piedra. According with literature, there is no record of isolation of this agent from mastitis in Brazil. This fact confirms the importance of microbiological studies to lead the treatment correctly to prevent the increase of bacterial resistance and secondary fungal infections that uses the inefficient antimicrobial as substratum for its development.
Ocurrence of clinical and subclinical mastitis in dairy herd caused by Trichosporon beigelii
Keywords: Fungal mastitis; Trichosporon beigelii; Bacteria (microorganisms); Fungi